Food and Nutritional Education actions for officers of the Brazilian Army: an experience report (Research, Society and Development, 2019)
The present work aimed at externalizing the practical experience of Food and Nutrition Education actions for workers occurred through an intervention carried out with officers of the Brazilian Army. The intervention addressed actions to recognize the routine and general characteristics of the commensals and the Food Unit that serves them, followed by the elucidation, through intervention, with active participation of the listeners, about adequate food practices and possible to be adopted by them in order to to provide better quality of life for the diners and the best cost benefit to the company. Finally, a questionnaire was applied with questions inherent to the subjects that were treated at the time of the intervention. The results achieved with the intervention were satisfactory and reinforce the importance of the EAN.